Clinical Features and Molecular Markers on Diffuse Midline Gliomas With H3K27M Mutations: A 43 Cases Retrospective Cohort Study - Wang, Yuan; Feng, Lan-lan; Ji, Pei-gang; Liu, Jing-hui; Guo, Shao-chun; Zhai, Yu-long; Sankey, Eric W.; Wang, Yue; Xue, Yan-rong; Wang, Na; Lou, Miao; Xu, Meng; et al. (Frontiers in Oncology, 2021)
Purpose: Diffuse midline gliomas (DMG) with H3K27M mutations have been identified as a rare distinctive entity with unique genetic features, varied molecular alterations, and poor prognosis. The current study aimed to evaluate the clinical characteristics and profile of molecular markers on patients with a DMG harboring H3K27M mutations, and explore the impact of this genetic makeup on overall survival. Methods: We retrospectively analyzed 43 consecutive patients diagnosed with a DMG harboring H3K27M mutations (age range 3 to 75 years) and treated in a tertiary institution within China between Jan 2017 to Dec 2019. Various clinical and molecular factors were evaluated to assess their prognostic value in this unique patient cohort. Results: The median overall survival (OS) was 12.83 months. Preoperative Karnofsky Performance Score (KPS) and adjuvant radiotherapy were found to be independent clinical parameters influencing the OS by multivariate analysis (p=0.027 and p<0.001 respectively). Whereas extent of tumor resection failed to demonstrate statistical significance. For molecular markers, P53 overexpression was identified as a negative prognostic factor for overall survival by multivariate analysis (p=0.030). Conclusion: Low preoperative KPS, absence of radiotherapy and P53 overexpression were identified as predictors of a dismal overall survival in patients with DMG and H3K27M mutations.